Economic burden of respiratory syncytial and parainfluenza viruses in children of upper-middle-income countries: a systematic review - Rocha-Filho, César Ramos; Ramalho, Gabriel Sodré; Martins, Johnny Wallef Leite [UNESP]; Lucchetta, Rosa Camila [UNESP]; Pinto, Ana Carolina Pereira Nunes; da Rocha, Aline Pereira; Trevisani, Giulia Fernandes Moça; de Assis Reis, Felipe Sebastião; Ferla, Laura Jantsch; de Carvalho Mastroianni, Patrícia [UNESP]; Correa, Luci; Saconato, Humberto; et al. (Elsevier, 2023)
OBJECTIVE: To identify and assess the current evidence available about the costs of managing hospitalized pediatric patients diagnosed with Respiratory Syncytial Virus (RSV) and Parainfluenza Virus Type 3 (PIV3) in upper-middle-income countries. METHODS: The authors conducted a systematic review across seven key databases from database inception to July 2022. Costs extracted were converted into 2022 International Dollars using the Purchasing Power Parity-adjusted. PROSPERO identifier: CRD42020225757. RESULTS: No eligible study for PIV3 was recovered. For RSV, cost analysis and COI studies were performed for populations in Colombia, China, Malaysia, and Mexico. Comparing the total economic impact, the lowest cost per patient at the pediatric ward was observed in Malaysia ($ 347.60), while the highest was in Colombia ($ 709.66). On the other hand, at pediatric ICU, the lowest cost was observed in China ($ 1068.26), while the highest was in Mexico ($ 3815.56). Although there is no consensus on the major cost driver, all included studies described that the medications (treatment) consumed over 30% of the total cost. A high rate of inappropriate prescription drugs was observed. CONCLUSION: The present study highlighted how RSV infection represents a substantial economic burden to health care systems and to society. The findings of the included studies suggest a possible association between baseline risk status and expenditures. Moreover, it was observed that an important amount of the cost is destinated to treatments that have no evidence or support in most clinical practice guidelines.